Actively triggered 4d cone‐beam CT acquisition. Issue 9 (12th August 2013) - Fast, Martin F.; Wisotzky, Eric; Oelfke, Uwe; Nill, Simeon
Abstract : Purpose: : 4d cone‐beam computed tomography (CBCT) scans are usually reconstructed by extracting the motion information from the 2d projections or an external surrogate signal, and binning the individual projections into multiple respiratory phases. In this "after‐the‐fact" binning approach, however, projections are unevenly distributed over respiratory phases resulting in inefficient utilization of imaging dose. To avoid excess dose in certain respiratory phases, and poor image quality due to a lack of projections in others, the authors have developed a novel 4d CBCT acquisition framework which actively triggers 2d projections based on the forward‐predicted position of the tumor. Methods: : The forward‐prediction of the tumor position was independently established using either (i) an electromagnetic (EM) tracking system based on implanted EM‐transponders which act as a surrogate for the tumor position, or (ii) an external motion sensor measuring the chest‐wall displacement and correlating this external motion to the phase‐shifted diaphragm motion derived from the acquired images. In order to avoid EM‐induced artifacts in the imaging detector, the authors devised a simple but effective "Faraday" shielding cage. The authors demonstrated the feasibility of their acquisition strategy by scanning an anthropomorphic lung phantom moving on 1d or 2d sinusoidal trajectories. Results: : With both tumor position devices, the authors were able to acquire 4d CBCTs free of motion blurring. For scans based on the EM tracking system, reconstruction artifacts stemming from the presence of the EM‐array and the EM‐transponders were greatly reduced using newly developed correction algorithms. By tuning the imaging frequency independently for each respiratory phase prior to acquisition, it was possible to harmonize the number of projections over respiratory phases. Depending on the breathing period (3.5 or 5 s) and the gantry rotation time (4 or 5 min), between ∼90 and 145 projections were acquired per respiratory phase resulting in a dose of ∼1.7–2.6 mGy per respiratory phase. Further dose savings and decreases in the scanning time are possible by acquiring only a subset of all respiratory phases, for example, peak‐exhale and peak‐inhale only scans. Conclusions: : This study is the first experimental demonstration of a new 4d CBCT acquisition paradigm in which imaging dose is efficiently utilized by actively triggering only those projections that are desired for the reconstruction process.